Making Sense of Scènes à Faire Through the Lens of Feist - Clarida, Robert W. (The Columbia Journal of Law & the Arts, 2020)
Scènes à faire: what is it, and why do we need a French name for it? Because when we explain it in English it doesn’t make any sense at all. Scènes à faire, Black’s Law Dictionary says, means “standard or general themes that are common to a wide variety of works and therefore are not copyrightable.” A number of other definitions of the term similarly deny copyrightability. For example, this is from a First Circuit case: the court “denie[d] copyright protection to elements of a work that are for all practical purposes indispensable, or at least customary, in the treatment of a given subject matter.” So again, we deny copyright protection. As Dale Cendali spoke to moments ago, most courts don’t look at it that way. The majority view is that it does not invalidate the copyright; it’s not a question of copyrightability. It’s a question of what is infringing activity and whether sharing this element actually rises to the level of infringement or not, not whether the scène à faire is copyrightable.